Cumulative viral evolutionary changes in chronic hepatitis B virus infection precedes hepatitis B e antigen seroconversion. Issue 9 (15th December 2012) - Cheng, Yan; Guindon, Stephane; Rodrigo, Allen; Wee, Lin Ying; Inoue, Masafumi; Thompson, Alex J V; Locarnini, Stephen; Lim, Seng Gee
Abstract : Objective: To examine viral evolutionary changes and their relationship to hepatitis B e antigen (HBeAg) seroconversion. Design: A matched case–control study of HBeAg seroconverters (n=8) and non-seroconverters (n=7) with adequate stored sera before seroconversion was performed. Nested PCR, cloning and sequencing of hepatitis B virus (HBV) precore/core gene was performed. Sequences were aligned using Clustal X2.0, followed by construction of phylogenetic trees using Pebble 1.0. Viral diversity, evolutionary rates and positive selection were then analysed. Results: Baseline HBV quasispecies viral diversity was identical in seroconverters and non-seroconverters 10 years before seroconversion but started to increase approximately 3 years later. Concurrently, precore stop codon (PSC) mutations appeared. Some 2 years later, HBV-DNA declined, together with a dramatic reduction in HBeAg titres. Just before HBeAg seroconversion, seroconverters had HBV-DNA levels 2 log lower (p=0.008), HBeAg titres 310-fold smaller (p=0.02), PSC mutations > 25% (p<0.001), viral evolution 8.1-fold higher (p=0.01) and viral diversity 2.9-fold higher (p<0.001), compared to non-seroconverters, with a 9.3-fold higher viral diversity than baseline (p=0.011). Phylogenetic trees in seroconverters showed clustering of separate time points and longer branch lengths than non-seroconverters (p=0.01). Positive selection was detected in five of eight seroconverters but none in non-seroconverters (p=0.026). There was significant negative correlation between viral diversity (rs =−0.60, p<0.001) and HBV-DNA or HBeAg (rs =−0.58, p=0.006) levels; and positive correlation with PSC mutations (rs =0.38, p=0.009). Over time, the significant positive correlation was viral diversity (rs =0.65, p<0.001), while negative correlation was HBV-DNA (rs =−0.627, p<0.001) and HBeAg levels (rs =−0.512, p=0.015). Conclusions: Cumulative viral evolutionary changes that precede HBeAg seroconversion provide insights into this event that may have implications for therapy.